2005
DOI: 10.1007/s10763-004-6828-7
|View full text |Cite
|
Sign up to set email alerts
|

Using ARCS Model to Promote 11th Graders' Motivation and Achievement in Learning about Acids and Bases

Abstract: The purposes of this study are: to apply the ARCS model in designing an acid and bases unit, and to assess a single class of 11th graders for motivation and achievement outcomes before and after ARCS instruction. Four essential strategies for designing motivation instruction in the ARCS model were: Attention, Relevance, Confidence, and Satisfaction. We used the ARCS model in designing a 10-hour acids and bases lesson for one class of 11th graders with low interest and motivation in chemistry learning. Both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 13 publications
1
31
0
4
Order By: Relevance
“…More specifically, the APA's messages were based on the design guidelines for the relevance and confidence components of the ARCS, which address perceptions of task relevance and self-efficacy. Several (non-agent) studies have reported significant effects of ARCS strategies on these motivational constructs (e.g., Feng and Tuan 2005;Huett et al 2008;Keller and Suzuki 2004;Loorbach et al 2007Loorbach et al , 2006Newby 1991;Song and Keller 2001). Specifically, the APA's messages were designed to inform students about task relevance by addressing goal orientation, motive matching and familiarity.…”
Section: Experimental Design and Research Questionsmentioning
confidence: 99%
“…More specifically, the APA's messages were based on the design guidelines for the relevance and confidence components of the ARCS, which address perceptions of task relevance and self-efficacy. Several (non-agent) studies have reported significant effects of ARCS strategies on these motivational constructs (e.g., Feng and Tuan 2005;Huett et al 2008;Keller and Suzuki 2004;Loorbach et al 2007Loorbach et al , 2006Newby 1991;Song and Keller 2001). Specifically, the APA's messages were designed to inform students about task relevance by addressing goal orientation, motive matching and familiarity.…”
Section: Experimental Design and Research Questionsmentioning
confidence: 99%
“…Additionally, this model [53] provides different strategies to enhance the motivational appeal of instruction and is based upon a solid empirical validation ( [54,55]). Its usefulness has been demonstrated in field studies [56], especially in science education research ( [57,58]). The motivational situation in our out-of-school laboratory is consistent with the ARCS model.…”
Section: Figmentioning
confidence: 99%
“…Also, several of these studies emphasized that some alternative conceptions were still robust to change even after the instruction (Kala et al, 2013;Özmen, Demircioğlu, & Coll, 2009). For chemistry attitude studies, some found positive attitudinal change towards chemistry (Botton, 1995;Feng & Tuan, 2005) but others elicited no attitudinal change towards chemistry (Üce & Sarıçayır, 2002). This inconsistency needs still to be clarified.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%